Sodium Imbalance as a Marker of Prognosis of Outcome in Patients with Traumatic Brain Injury - Khambhu, Bikesh; Jha, Rajiv; Bista, Prakash (Nepal Journal of Neuroscience, 2020)
Introduction: Sodium imbalance in post-traumatic brain injury is not uncommon. It’s early detection and treatment is vital as it increases morbidity and mortality if not treated on time. We study the effect of Sodium imbalance as a predictor of outcome in these patients.Methods and Materials: Patients diagnosed with traumatic brain injury (TBI) admitted to Neurosurgery department were included in this study. Traumatic brain injury cases managed between 1st Baisakh 2074 B.S. and 29th Chaitra 2074 B.S. were analyzed prospectively.  Glasgow Coma Scale, Computed Tomography scan of head, duration of hospital and Intensive Care Unit (ICU) stay, and Glasgow Outcome Scale in relation to sodium imbalance measured within 24 hours of injury were assessed. Mortality and morbidity were measured using Glasgow Outcome Scale (GOS).Results: A total of 100 patients with traumatic brain injury admitted in the Neurosurgery department of Bir Hospital were included in this study. Sixty seven cases were categorized as mild, 18 as moderate and 15 as severe according to the severity of TBI. The maximum serum sodium level observed was 168 and lowest was 110 mmol/l. The association of sodium imbalance with severity of head injury was found to be statistically significant. The sensitivity of sodium imbalance measured within 24 hours of injury in prognosticating outcome of patient till death or before discharge from hospital on the basis of GOS and Neuro ICU stay day is significant with p value